2015
DOI: 10.1515/bot-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

European aquaculture of sugar kelp (Saccharina latissima) for food industries: iodine content and epiphytic animals as major problems

Abstract: There is little use of cultivated kelp including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
53
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 25 publications
10
53
2
Order By: Relevance
“…(; for L. digitata from Shetland, UK, Helgoland, Germany, and Brittany, France) nor this study could establish a clear relationship between “site” (or associated confounding variables) and the iodine content of brown, red and green macroalgae. Although salinity previously appeared to affect iodine concentrations in Laminariales (Kylin , Lüning and Mortensen ) and a 24‐h exposure of L. digitata to decreased salinities caused an increased net I − efflux rate (Nitschke and Stengel ), no obvious trends were observed between sampling locations in this study.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…(; for L. digitata from Shetland, UK, Helgoland, Germany, and Brittany, France) nor this study could establish a clear relationship between “site” (or associated confounding variables) and the iodine content of brown, red and green macroalgae. Although salinity previously appeared to affect iodine concentrations in Laminariales (Kylin , Lüning and Mortensen ) and a 24‐h exposure of L. digitata to decreased salinities caused an increased net I − efflux rate (Nitschke and Stengel ), no obvious trends were observed between sampling locations in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…Similarly, spatial variation reported for European kelp populations may be associated with exposure (wave action), duration of winter (Ar Gall et al. ) or the local salinity regime (Kylin , Nitschke and Stengel , Lüning and Mortensen ). In addition, elevated molecular iodine (I 2 ) concentrations in air were observed above emersed seaweed beds (McFiggans et al.…”
mentioning
confidence: 94%
“…Studies have reported that brown macroalgae, particularly kelps such as Laminaria and Saccharina, are rich in minerals such as I (Holdt & Kraan, 2011;Lüning & Mortensen, 2015;Maehre et al, 2014;Makkar et al, 2016;Teas, Pino, Critchley, & Braverman, 2004). In northwest Europe, Holdt and Kraan (2011) reported I content in Laminaria and Saccharina (species unspecified) of 230 to 12,000 mg/kg dw.…”
Section: 123mentioning
confidence: 99%
“…In Norway, the presence of epiphytic invertebrates, especially bryozoans (e.g. Membranipora membranacea and Electra pilosa), but also blue mussels (Mytilus edulis), hydroids and fouling macroalgae has been reported for sugar kelp cultivated at sea during summer months (Forbord et al 2012;Handå et al 2013;Lüning and Mortensen 2015;Førde et al 2016). In worst case scenarios, such fouling may lead to extensive blade damage and loss of biomass or considerable quality deterioration.…”
Section: Epiphytes and Diseasesmentioning
confidence: 99%
“…However, few studies about negative consequences of consuming seaweeds have been carried out, but among the best documented are effects of high iodine content in some brown algae (Lüning and Mortensen 2015;Desideri et al 2016). The potentially mitigating effects of primary processing of edible seaweeds on their content of toxins as well as antinutrients (i.e.…”
Section: Risk Assessment 2-product Relatedmentioning
confidence: 99%